Pre-Treatment Air Payau Dengan Koagulan Tepung Jagung Dan Filtrasi Dengan Membran Ultrafiltrasi Sistem Aliran Crossflow - Kardo Kardo; Syarfi Daud; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The coastal area are poor raw water eligible to be used as a standard raw water based on PERMENKES No. 492/210 and PP No. 82/2001. This area typically used brackish water daily needs. Due to the presence of sea water intrussion in to wells. The brackish water are not suitable to be use continue. It therefore reguirestreatment to get suitable water. Pre-treatment of brackish water with contrarch as coagulant and filtration membrane as alternative technology to be developed in water treatment. This research aims to be knowing the influence of coagulant dose variation, the transmembrane flux and rejction against of salinity, turbidity,COD, TSS, and pH. This result are showing the best reduction of pre-treatment process in 50 ppm therefore efectivity each other are salinity 23,61%, turbidity 43,64%, COD 83,58%, TSS 98,03%, and pH 12,05%. The filtration with membrane each parameter are salinity 89,09%, turbidity 88,94%, COD 58%, TSS 85,71 and pH 27,10%. Flux value obtained pressure is 1,5 bar that is 276,506l/m2.jam.Keywords: Brackish Water, COD (Chemical Oxygent Demand), Corn Starch, Pre-treatment, Ultrafiltration Membrane, Salinity, TSS (Total Suspended Solid), Turbidity